Texas rising : the epic true story of the Lone Star Republic and the rise of the Texas Rangers, 1836-1846 - Moore, Stephen L. (William Morrow, an imprint of HarperCollinsPublishers, 2015)
Texas historian Stephen L. Moore's Texas Rising, the official companion to the epic History Channel series of the same name, brings to life the violent Texas frontier and the Rangers' heroic deeds during the Texas Revolution.